Personnel Management Mechanisms and Public Service Delivery in the Rivers State Local Government Service Commission - Grace John Mark (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examined personnel management mechanisms and public service delivery in the Rivers State Local Government Service Commission between 2014 and 2024. The study specifically evaluated the impact of promotion criteria and practices on staff productivity and public service delivery, and examined the effect of disciplinary and control mechanisms on service delivery within the Commission. Two research questions and two hypotheses guided the study. The study adopted Weberian Bureaucratic Theory as its theoretical framework, emphasizing meritocracy, accountability, hierarchy, and standardized administrative procedures in public sector management. A survey research design was adopted, while data were collected through structured questionnaires administered to staff in Obio-Akpor, Khana, and Ahoada East Local Government Areas. From a population of 937,285, a sample size of 400 respondents was determined using Taro Yamane’s formula, out of which 390 questionnaires were successfully retrieved. Data were analyzed using descriptive statistics and Pearson Product Moment Correlation with the aid of SPSS version 27. The findings revealed that promotion and performance appraisal mechanisms were largely merit-based, transparent, and effective in motivating employees, improving morale, accountability, productivity, and public service delivery. The study further established that disciplinary and control mechanisms significantly promoted compliance, organizational integrity, and ethical conduct within the Commission. Correlation results indicated strong positive relationships between promotion practices, disciplinary mechanisms, and public service delivery. However, occasional inconsistencies, perceived favoritism, and uneven enforcement of rules were identified as challenges affecting employee confidence. The study concluded that effective personnel management mechanisms are essential for improving administrative performance and public service delivery in the Rivers State Local Government Service Commission. The study recommended strengthened transparency, fairness, and consistency in promotion, appraisal, and disciplinary procedures.